Gemini Near Infrared Spectrograph Distant Quasar Survey: Initial Results - Matthews, Brandon (2019)
We present the first installment of spectroscopic measurements performed with the Gemini Near Infrared Spectrograph Distant Quasar Survey (GNIRS-DQS). This is a three-year project, launched in 2017, aimed at obtaining high quality near-infrared spectroscopy of 416 Sloan Digital Sky Survey (SDSS) quasars between redshifts of 1.5 and 3.5 in the ~1.0-2.5 μm band. A combination of the GNIRS and SDSS spectra will cover principal quasar diagnostic features, chiefly the C IV, Mg II, Hβ, and [O III] emission lines, in each source. The spectral inventory will be utilized primarily to develop prescriptions for obtaining more accurate and precise redshifts, black hole masses, and accretion rates for all quasars. Additionally, our measurements will facilitate a more complete understanding of how the rest-frame UV-optical spectral properties of quasars depend on redshift and luminosity, and test whether the physical properties of the quasar central engine evolve over cosmic time. Our raw data are immediately available to the public through the Gemini Observatory Archive, and our final reduced and calibrated spectra will be made available shortly thereafter on a dedicated public website. This work is supported by National Science Foundation grants AST-1815281 and AST-1815645.